THROWN AWAY AND THROUGH A FIRE OF RUDYARD KIPLING: AESTHETICS EVIDENCES OF POPULAR SHORT STORIES - Taufiqurrohman Taufiqurrohman (Universitas Islam Nahdlatul Ulama Jepara, 2016)
This essay tries todeconstruct the thinking way of elite literary writers and readers in dominating the aesthetic claime of literary works, especially in short stories. The writer of this essay has used the content of two short stories to be explored. They are Thrown Away and Through A Fire written by Rudyard Kipling. The imitative and imaginative aesthetic aspect of both stories were analyzed to reach the finding signs of aesthetic proof. Imitative aspect uses the imitations to nature phenomena while Imaginative one uses symbols used by human. The result of analysis shows that both aspects lie in the content of both short stories. Thrown Away uses the beauty of tragic. Kipling had used both imitative and imaginative aspects to enhanced the tragic life of the main character. Through A Fire has used circle of fire in the content of its story. Whole plotting of it is full of fire either it is fire naturally or it is symbolically. The conclusion is enough to be the evidences that popular short stories also have aesthetic aspects.